Managing the Oil Revenue Boom : The Role of Fiscal Institutions - Villafuerte, Mauricio (Occasional Papers; Occasional Paper ;, 2008)
Oil-producing countries have benefited from rising oil prices in recent years. The increase in oil exports and oil revenues has had major implications for these countries. These developments have revealed how governments manage their fiscal policies in light of changing oil-market conditions and the role of special fiscal institutions (SFIs). In this Occasional Paper, IMF experts examine the fiscal response of oil-producing countries to the recent oil boom and the role of SFIs in fiscal management, they review the experiences of selected countries, and they draw general lessons. In doing so, they link findings on best practice in the design of SFIs with broader fiscal management advice.